Changes in Root–Shoot Allometric Relations in Alpine Norway Spruce Trees After Strip Cutting - Nikolova, Petia Simeonova; Geyer, Jan; Brang, Peter; Cherubini, Paolo; Zimmermann, Stephan; Gärtner, Holger (Frontiers in Plant Science, 2021)
Silvicultural interventions such as strip cuttings can change resource availability of the edge trees. This may alter tree allometry, as light regime, water and nutrient availability can change at the forest edge. An increased root growth may optimize resource uptake and/or enhance tree anchorage to withstand the altered wind regime. However, little is known about the patterns of the root-shoot allometric responses to strip cuttings. In three alpine stands differing in climate, site productivity and stand characteristics, we selected 71 Norway spruce trees and took increment cores from stems, root collars and main roots. This enabled us to study changes in the root-stem allometry over a period of 46 years and short-term allometric responses to intervention. The effects of cutting were compared between edge trees and trees from the stand interior in a 10-year period before and after intervention. The long-term allocation to roots increased with stem diameter, with the strongest effects on the regularly managed stand with the tallest and largest trees. These results support the allometric biomass partitioning theory, which postulates resource allocation patterns between different plant organs to depend on plant size. Strip cutting on north-facing slopes boosted edge-tree growth in all plant compartments and enhanced allocation to roots. This change in allometry started two years after cutting but disappeared seven-to-eight years later. In the post-cutting period, highest root-shoot increase was observed in the small trees independent on the site. This indicates the change in growing conditions to have strongest effects in formerly suppressed trees. Thus, the effect of such acclimation on the windfirmness of subdominant spruce trees is a question with high importance for optimizing cutting layouts in lowering post-cutting vulnerability to disturbance. The results from our case study contribute to a better understanding of the structural acclimation of spruce trees from high-elevation forests to new forest edges. However, for a more mechanistic understanding of environmental drivers, further analyses of tree-ring stable isotopes are recommended.